Phoebe the spy - Griffin, Judith Berry; Tomes, Margot (New York : Scholastic, 1977)
During the Revolution, Phoebe Fraunces has a chance to save the life of General George Washington while he has dinner at Mortier House in New York City.
Original title: Phoebe and the general.
4.0
3-6
Keywords: Fraunces, Phoebe -- Juvenile literature; Washington, George, -- 1732-1799 -- Juvenile literature; Fraunces, Phoebe; Washington, George, -- 1732-1799.; Spies -- United States -- Juvenile literature; African American girls -- New York (State) -- New York -- Juvenile literature; African Americans -- New York (State) -- New York -- Juvenile literature; Spies; African Americans; Women; United States -- History -- Revolution, 1775-1783 -- Juvenile literature; United States -- History -- Revolution, 1775-1783.